2019
DOI: 10.11604/pamj.2019.34.58.14472
|View full text |Cite
|
Sign up to set email alerts
|

Étalonnage du test des cinq mots dans une population tunisienne de sujets sains

Abstract: IntroductionLe test des 5 mots (T5M) est un test de mémoire permettant d’explorer la mémoire verbale épisodique. Il évalue la mémoire des sujets ayant une plainte mnésique, en particulier dans le cadre du diagnostic de la maladie d’Alzheimer où il se révèle sensible et spécifique. L’objectif de notre travail est d’étudier l’effet des différents paramètres sociodémographiques sur les performances, d’établir des normes adaptées à la population tunisienne et de comparer nos résultats aux études précédentes.Méthod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A Tunisian research group concluded that the standard cut-off of 9/10 could be sensitive enough in a population of young Tunisian adults (< 50 years) who had not completed their primary education. In this study the five words were however translated into Arab [30]. The Dubois' five-word testing was the only test used in our study which required the ability to read.…”
Section: Methodsmentioning
confidence: 99%
“…A Tunisian research group concluded that the standard cut-off of 9/10 could be sensitive enough in a population of young Tunisian adults (< 50 years) who had not completed their primary education. In this study the five words were however translated into Arab [30]. The Dubois' five-word testing was the only test used in our study which required the ability to read.…”
Section: Methodsmentioning
confidence: 99%